The Evaluation of Thermal Comfort using a BIM-based Thermal Bridge Simulation - Rahadian, Erwin Yuniar; Sulistiawan, Agung Prabowo (Journal of Architectural Research and Education, 2019)
Global warming has become an important issue today, caused by the increasing demand for energy and humans lifestyle. To reduce the impact, more architects started to respond regarding environmental issues. The concept of green architecture promotes to solving this problem. Natural ventilation is the one of the concept green architecture. This research tends to look at the aspect of Thermal Comfort in naturally ventilated mosque buildings through the Thermal Bridges strategy. Naturally ventilated building tend to have better indoor air quality (IAQ), but worse thermal comfort. Therefore, this research investigates the range of acceptable temperature and calculate by BIM thermal bridge simulation to achieve thermal comfort for naturally ventilated mosque building. The method of analysis conducted is quantitative based on direct measurement of weather data and existing comfort conditions in the field, calculations, and simulations using Building Information Modeling (BIM). Data was collected through a field survey in Itenas Mosque Building and were used to develop and validate then using the BIM thermal bridge model for simulation. The data collected from field survey and in situ environmental measurement such as air temperature, relative humidity, and wind velocity. The thermal comfort prediction model was developed from statistical analysis of the field survey data. Based on the result of thermal Bridge simulation using BIM software required exchange material of the existing building to achieve thermal comfort.Â Keyword-Thermal comfort, Building Information Modelling, Thermal Bridge Simulation